Cultivating social occupations, spaces, and networks: service providers’ perspectives on enabling immigrants’ social participation/ Cultivando ocupações sociais, espaços e redes: as perspectivas dos prestadores de serviços sobre como possibilitar a participação social dos imigrantes - Huot, Suzanne; Brower, Jaqueline; Tham, Alex; Yekta, Atieh Razavi (Cadernos Brasileiros de Terapia Ocupacional, 2021)
Introduction: Immigrants may experience many barriers to social participation within host societies. Immigrants’ integration into Canadian society is supported through government-funded services. Objective: In the present study, we explored the perspectives of service providers working in community organizations regarding their role in enabling immigrants’ social participation through occupations in British Columbia, Canada. Method: Representatives from twenty different organizations providing services to the community participated in a constructivist qualitative study aiming to uncover aspects shaping opportunities for occupational participation provided for immigrants. Results: Drawing on semistructured interviews and using thematic analysis, we identified three main themes relating to cultivating social occupations, spaces, and networks. Findings illustrate that service providers’ cultivation of these opportunities can support immigrants’ desired social roles and social identities, further enabling their participation in receiving societies. Conclusion: Emphasis upon supporting socio-economic integration into society appears to limit a client-centred approach to developing opportunities for social participation through occupation. Implications for occupational therapists and scientists are discussed.